HUBUNGAN KELINCAHAN DENGAN KEMAMPUAN DRIBBLING SEPAKBOLA PADA SISWA EKSTRAKURIKULER SMP NEGERI 2 KUBU - Supian '; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The background of the problem in this research is not maximal yet soccer dribbling ability of being owned by the student extracurricular SMPN 2 Kubu. Of the few opportunities to attack by dribbling readable way and captured by the opponent. This problem is evident from observations of researchers at the time of the try out and the game, it is suspected because of the agility possessed by the students. Therefore, the purpose of this study was to determine whether there is a corelation with the dribbling soccer ability in extracurricular students SMPN 2 Kubu. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As the independent variable (X) is agility, while the dependent variable (Y) is a soccer dribbling skills. This research data obtained from the tests using dodging run test and dribbling soccer test. The sample in this research is the students who follow football extracurricular totaling 30 people (total sampling). Based on the research results can be concluded as follows: